[着魔 : 论高行健的 "没有主义" 和 "毛体"] = Obsession : on Gao Xingjian’s “without Isms” and “Maoist style” - 許维贤 Hee, Wai Siam (2015)
王德威曾把夏志清的 Obsession with China（丁福祥和潘铭燊译成“感时忧国”，本文重译成“对中国着魔”）与詹明信的 National allegory （‘民族寓言’）论相提并论，批评詹明信的理论自谓激进，其实泄露了再现论的谜思，比诸夏志清的“对中国着魔”论，并未见有真正突破。王德威指出夏志清至少指出“对中国着魔”的缺点-如笔锋粗糙、缺乏‘象征’密度，但这些作品往往却被詹明信的民族寓言视之为歌颂对象。高行健的小说笔锋也相当粗糙，甚至亦缺乏‘象征’密度。本文从弗洛伊德对“着魔官能症”（Obsessional Neurosis）的论述，探析高行健作品中的“毛体”—从毛泽东的遗体到毛话语，如何渗透和穿透高行健的文体—从“没有主义”的论述到其小说。高过于简单地把毛话语的暴力和个人一切欲望的受挫紧紧连锁成因果关系，这些关于个人利比多与民族政治角力的文本，往往指向一种作为第三世界的中国的民间文化和社会形态持续遭受现代性冲击的寓言。高在小说里总是情不自禁直接把自己揪到作品前发出宣言，这不过是另外一种“文以载道”。总体小说实践倾向于“民族寓言”，但其小说美学却对“国家神话”和中国民族主义恨之入骨。本文把这种始终摇摆在背离“对中国着魔”和“民族寓言”之间的间隙状态称之为“精神着魔‘中国’”。高无法超越他爱恨的逃亡对象，而精神着魔召唤的对象不过是在“中国”或“毛泽东”或“女人”这三大能指之间不断互相置换和错位而已。David Der-wei Wang has ever held C.T. Hsia's "Obsession with China" comparable to Fredric Jameson's "national allegory," and made the critical comment that despite the self-asserted radicalism in his theory, Jameson has actually exposed the myth of representation theory. Jameson's theory doesn't show any genuine breakthrough when compared with C. T. Hsia's "Obsession with China." Wang pointed out that Hsia was at least able to name various shortcomings in "Obsession with China," such as rough and loose symbolism. However, works like that have been always taken by Jameson as the national allegory and meant to be praised. The style of Gao Xingjian's novels is also quite rough and even loose in symbolism. This article tries to approach the "Maoist style"—from Mao Zedong's remains to Mao's words—in Gao's literary works in the light of Freud's discourse on obsessional neurosis, and analyze how it infiltrates and penetrates Gao Xingjian's literary style—from his discourse "Without Isms" to his novels. Gao is so ready to causally link up the violence of Mao's words with any obstructed desire of a person. All the texts about the struggle of personal libido against national politics always allude to an allegory of the folk culture and social formation of China as a third-world country subject to the continuous impact of modernity. In his novels, Gao is always unable to restrain himself from inserting himself directly into the front stage of his works to make statements. It's nothing but another kind of "writings serving purpose of truth." The overall practice of his novels is oriented towards being "national allegory," while the aesthetics of his novels bears such a grudge against "national myth" and Chinese nationalism. This state of constant oscillation in the gap between the betrayal of "Obsession with China" and "national allegory" is called "spiritual obsession with 'China'" in this article. As Gao is unable to surpass the object that his love and hatred try to escape from, his spiritual obsession is just caught up in the displaced and misplaced play among the three major signifiers: "China," "Mao Zedong," and "woman."